Organizational Happiness Index (OHI): Conceptualization and operationalization of measurement among employees in services industry / Muhamad Khalil Omar, Ridhawati Zakaria and Azzarina Zakaria - Omar, Muhamad Khalil; Zakaria, Ridhawati; Zakaria, Azzarina (Penerbit UiTM (UiTM Press), 2016)
The issue of happiness in organization has been debated among academicians f practitioners, and policy makers nowadays. This is because the concept of happiness is very likely to help guide progress towards sustainable development. Whereas sustainable development entails all parties especially public and private organizations to balance economic, social and environmental objectives in a holistic manner. When organizations pursue economic wealth in a lopsided manner, overriding social and environmental objectives, the results often negatively impact human wellbeing inside and outside organizations such as employees, customers and communities. Therefore, there is a strong need for organizations to ensure the sustainability of their development by understanding the level of happiness of their workers. However, evaluating happiness could be inconclusive since available measurements were one-dimensional and non-academically validated. Hence, the objective of this study is to propose a systematic measurement of organizational happiness index that is conceptualized using 3-dimensional Authentic Happiness theory which to be operationalized in service industries settings as these industries employ substantial number of human resources. This study also aims to quantitatively produce the index for each participating service organization besides analyzing the identified research framework using structural equation modeling, where studies emphasizing such an approach are relatively scarce.